أبو عبداللە محمد بن الحداد الشعر و الشاعر - توفيق, عمر ابراهيم (Sulaimani Journal for Humanities, 2003)
biography of an Andalusian poet , Abdulla Bin Al Haddad ( died 480 H), who lived during a period of gloomy conflict Known as (Assir - Altawaif - Era of sect). The research studies his poetic perposes profoundly, particularly at the one he maotered well, which can be called (Algazal Bilnasraniyat – love poetry on christian ladies), where he Succeeded in conveying portraits of customs and rites of christianity in to the abrabic literature, besides the an alysing Selected Samples of his verses.This research concludes with an appendia contaming about 396 lines his verses found with in page of liteary and historical books .